Efektivitas Penerapan Tarif PPh OP UU No.7 Tahun 2021 Pada Pertumbuhan WP Dan Penerimaan PPh 21 - Patriasih, Yasinta; Martaseli, Evi; Tanjung, Hendra (AKUNTANSI 45, 2023)
This study aims to explain the growth in the number of taxpayers and the effectiveness of income tax article 21 after the application of the personal income tax rate of Law Number 7 of 2021. The research method used in this research is descriptive qualitative method. The data collection methods in this study are observation, interview and documentation. The research data used are primary and secondary data. Primary data obtained from interviews with KPP Pratama Sukabumi and secondary data in the form of the number of registered taxpayers and the target and realization of income tax Article 21 revenue before and after the application of personal income tax rates in Law No. 7 of 2021. The results showed that the average growth in the number of individual taxpayers 17 months before the implementation and 17 after the implementation of the progressive rate of personal income tax in Law No. 7 of 2021 at KPP Pratama Sukabumi decreased in growth by 0.13% and the effectiveness of income tax article 21 revenue in 2022 was included in the criteria very effective with a percentage of effectiveness of 109.35% and until the data was obtained in May 2023 the effectiveness of revenue fell into the ineffective category with a percentage of effectiveness of 38.75%.